Private Electrical Utilities and Municipal Ownership in Ontario,1891-1900 - Dewar, Kenneth (Urban History Review / Revue d'histoire urbaine, 1983)
In June, 1897, the electrical utility companies of Ontario launched their first organized offensive against municipal ownership. Their objective was to secure an amendment to the Ontario Municipal Act that would protect the vested interests of local utilities and perhaps slow the reform movement then gathering momentum throughout the province. Two years later, they achieved success in the form of the so-called "Conmee Clauses", requiring municipalities to buy out privately owned local electrical and gas utilities before inaugurating their own systems. The industry united behind the campaign only with difficulty. Its spokesmen expressed a view of the role of the state at once flexible in its conception of the limits of government regulation, and fixed in its perception of government's responsibility to protect fundamental business interests. In the short term, opponents of the legislation were unable to prevent its passage; in the long term, this dispute was but one episode in the conflict over municipal ownership which culminated in the establishment of the Hydro-Electric Power Commission of Ontario.